A proposal of guidelines for the development of an indexing policy in university libraries: a verbal-protocol-based socio-cultural study - Dal'Evedove, Paula Regina; Lopes Fujita, Mariangela Spotti [UNESP] (Univ Zaragoza, 2017)
A set of eight guiding guidelines for the preparation of indexing policies in Brazilian university libraries is presented, as a result of a verbal-protocol study among a group of indexers from Brazilian university libraries.
Keywords: Subject cataloguing; Indexing policies; Verbal protocol; Sociocultural approach; University libraries; Brazil